2018
DOI: 10.3390/medicina54050088
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the CCR6-CCL20 Axis: A Potential Therapeutic Target in Inflammation and Cancer

Abstract: Prototypical functions of the chemokine receptor CCR6 include immune regulation by maneuvering cell chemotaxis and selective delimiting of the pro-inflammatory TH17 and regulatory Treg subsets during chronic or acute systemic inflammation. Inhibition of CCR6 is proposed to attenuate disease symptoms and promote recuperation of multiple inflammatory and autoimmune disorders. Prescription medicines with pharmacodynamics involving the inhibition of the chemokine axis CCR6–CCL20 are very limited. The development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…This study has highlighted a functional role for CCR6 in the pathogenicity of spontaneous chronic colitis and provides evidence that CCR6 could be utilised as a functional therapeutic target in IBD. The proven functional efficacy in CCR6-inhibition in psoriasis, rheumatoid arthritis, multiple sclerosis carcinoma and EAE, could be replicated in IBD as well [11]. Recent research had shown the direct involvement of CCR6 with AKT/mTOR pathway which contributes to the TH17/Treg imbalance which is considered as the prime immunological factor which decides the resolution of colitis [21] and needs further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This study has highlighted a functional role for CCR6 in the pathogenicity of spontaneous chronic colitis and provides evidence that CCR6 could be utilised as a functional therapeutic target in IBD. The proven functional efficacy in CCR6-inhibition in psoriasis, rheumatoid arthritis, multiple sclerosis carcinoma and EAE, could be replicated in IBD as well [11]. Recent research had shown the direct involvement of CCR6 with AKT/mTOR pathway which contributes to the TH17/Treg imbalance which is considered as the prime immunological factor which decides the resolution of colitis [21] and needs further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Not only colitis, but many other diseases relating to multi-organ pathologies are also influenced by the CCR6-CCL20 immune axis. Several autoimmune diseases such as experimental autoimmune encephalitis (EAE), rheumatoid arthritis (RA) and psoriasis have been shown to display reduced inflammation when CCR6 was inhibited in pre-clinical and clinical disease models [11]. Sixteen tractable CCR6 inhibitors have been introduced as a potential therapeutic option in those diseases [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations